2017
DOI: 10.1155/2017/9196528
|View full text |Cite
|
Sign up to set email alerts
|

The First Reported Case of Majocchi’s Granuloma withMalbrancheasp. in an Immunocompetent Patient

Abstract: Majocchi's granuloma is a rare condition in which a dermatophyte invades the deeper layers of the dermis and subcutaneous tissue and can often be misidentified and treated as eczema. It has a variable presentation ranging from cutaneous lesions to deeper infections in immunocompromised patients. No prior cases have described the formation of Majocchi's granuloma with the deuteromycetes, Malabranchea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Non-dermatophytic fungi such as those belonging to the genera Phoma and Aspergillus were also reported as etiological agents of MG. 9 , 67 Among the 33 cases that were reviewed, only one study reported the presence of a non-dermatophytic but keratinophilic fungus, a Malbranchea species, in an immunocompetent patient who had eczema as the underlying disease. 68 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Non-dermatophytic fungi such as those belonging to the genera Phoma and Aspergillus were also reported as etiological agents of MG. 9 , 67 Among the 33 cases that were reviewed, only one study reported the presence of a non-dermatophytic but keratinophilic fungus, a Malbranchea species, in an immunocompetent patient who had eczema as the underlying disease. 68 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Although ketoconazole was frequently used previously, about half of the patients reported today are treated with terbinafine (250 mg/day). 8 , 13 , 36 , 40 , 43 , 47 , 54 , 68 71 Other systemic antifungal drugs are itraconazole (100–200 mg/day), 32 , 44 , 53 , 72 griseofulvin (250–500 mg/day), 10 , 35 , 63 voriconazole, 73 and posaconazole. 28 Antifungal therapy should be continued until the lesions are completely resolved.…”
Section: Treatmentmentioning
confidence: 99%
“…More recently, Malbranchea spp. have been proposed as one of the causative agents of Majocchi's granuloma (Govind et al 2017;Durdu et al 2019). In a study of 245 patients with fungal saprophytic infections of nails and skin, Malbranchea spp.…”
Section: Introductionmentioning
confidence: 99%